Equilibrium drives of the low and high field side n = 2 plasma response and impact on global confinement. (31st March 2016) - Paz-Soldan, C.; Logan, N.C.; Haskey, S.R.; Nazikian, R.; Strait, E.J.; Chen, X.; Ferraro, N.M.; King, J.D.; Lyons, B.C.; Park, J.-K.
Abstract: The nature of the multi-modal n   =  2 plasma response and its impact on global confinement is studied as a function of the axisymmetric equilibrium pressure, edge safety factor, collisionality, and L-versus H-mode conditions. Varying the relative phase ( Δ ϕ U L ) between upper and lower in-vessel coils demonstrates that different n   =  2 poloidal spectra preferentially excite different plasma responses. These different plasma response modes are preferentially detected on the tokamak high-field side (HFS) or low-field side (LFS) midplanes, have different radial extents, couple differently to the resonant surfaces, and have variable impacts on edge stability and global confinement. In all equilibrium conditions studied, the observed confinement degradation shares the same Δ ϕ U L dependence as the coupling to the resonant surfaces given by both ideal (IPEC) and resistive (MARS-F) MHD computation. Varying the edge safety factor shifts the equilibrium field-line pitch and thus the Δ ϕ U L dependence of both the global confinement and the n   =  2 magnetic response. As edge safety factor is varied, modeling finds that the HFS response (but not the LFS response), the resonant surface coupling, and the edge displacements near the X-point all share the same Δ ϕ U L dependence. The LFS response magnitude is strongly sensitive to the core pressure and is insensitive to the collisionality and edge safety factor. This indicates that the LFS measurements are primarily sensitive to a pressure-driven kink-ballooning mode that couples to the core plasma. MHD modeling accurately reproduces these (and indeed all) LFS experimental trends and supports this interpretation. In contrast to the LFS, the HFS magnetic response and correlated global confinement impact is unchanged with plasma pressure, but is strongly reduced in high collisionality conditions in both H- and L-mode. This experimentally suggests the bootstrap current drives the HFS response through the kink-peeling mode drive, though surprisingly weak or no dependence on the bootstrap current is seen in modeling. Instead, modeling is revealed to be very sensitive to the details of the edge current profile and equilibrium truncation. Holding truncation fixed, most HFS experimental trends are not captured, thus demonstrating a stark contrast between the robustness of the HFS experimental results and the sensitivity of its computation.